Identification of Clinostomum complanatum (DIGENEA: CLINOSTOMIDAE) Infecting Anabas tes - Morina Riauwaty; Kurniasih Kurniasih; Joko Prastowo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2011)
The aim of study was to molecularly determine Clinostomum complanatum (Digenea: Clinostomidae) from freshwater fish in Yogyakarta and Riau, Indonesia.